The Urgency of Pre-Marital Counseling in Preventing Domestic Violence: A Case Study at the Office of Religious Affairs (KUA) in Mawasangka District, Central Buton - Dina Pratiwi; La Jusu; Abdul Kahar Syarifuddin (Social Science Academic, 2026)
Domestic violence remains a serious threat to family wellbeing in Indonesia. This study aims to analyze the key success factors of pre-marital guidance at the Office of Religious Affairs (KUA) of Mawasangka District in preventing domestic violence and to explore the value-internalization mechanisms that allow the preventive impact to endure without continued mentoring. The study employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with the head of the KUA, the marriage registrar (penghulu), and couples who participated in the guidance program, as well as documentation. Data analysis followed the model of Miles et al., comprising the stages of condensation, display, and conclusion drawing. Data validity was ensured through source and method triangulation, member checking, and peer debriefing. The results show five key success factors: strong institutional commitment, credible and high-quality facilitators, a comprehensive material structure, an interactive-participatory method, and support from a religious socio-cultural environment. The value-internalization mechanism occurs through cognitive-emotional-spiritual learning, self-reflection that builds personal awareness, concrete-applicative knowledge transfer, the formation of mutual commitment, and the cultivation of a continuous-learning mindset. These findings contribute to SDGs Goals 3, 5, and 16 by presenting a cost-effective and replicable model of pre-marital guidance as a strategy for preventing domestic violence. This study extends the theoretical framework on preventive educational programs by showing that maximum success can be achieved even under limited resources through an effective value-internalization mechanism.